Application of Lattice Boltzmann Method to Simulation of Compressible Turbulent Flow (Communications in Computational Physics, 2010)
The main goal of this paper is to develop the coupled double-distribution-function(DDF) lattice Boltzmann method (LBM) for simulation of subsonic and transonicturbulent flows. In the present study, we adopt the second-order implicit-explicit(IMEX) Runge-Kutta schemes for time discretization and the Non-Oscillatory and Non-Free-ParametersDissipative (NND) finite difference scheme for space discretization.The Sutherland's law is used for expressing the viscosity of the fluid due to considerabletemperature change. Also, the Spalart-Allmaras (SA) turbulence model is incorporatedin order for the turbulent flow effect to be pronounced. Numerical experimentsare performed on different turbulent compressible flows around a NACA0012airfoil with body-fitted grid. Our numerical results are found to be in good agreementwith experiment data and/or other numerical solutions, demonstrating the applicabilityof the method presented in this study to simulations of both subsonic and transonicturbulent flows.